M Muhammad Ali Jinnah’s Struggle In The Formation Of The Pakistan State - Sulaiman, Hasti (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2022)
This study aims to determine the educational history, career in the political world of Muhammad Ali Jinnah, the factors that caused the separation of the State of Pakistan and the State of India and the struggle of Muhammad Ali Jinnah in the formation of the State of Pakistan. The type of research used is library research. With a qualitative research method that is descriptive analytic. Library research is research whose data collection is carried out by collecting data from various literatures related to the history of education, career in politics and the struggle of Muhammad Ali Jinnah in the formation of the Pakistani state. The data that has been obtained is then analyzed using a historical approach. The results of this study can illustrate that Muhammad Ali Jinnah attended junior high school at one of the Islamic madrasas, namelyat Sind Madrasatul Islam. At the age of 15, Jinnah continued her high school at the Christian missionary school (mission high school) in Karachi, after graduating from high school, she continued her studies at the University of Mumbai and majored in Law. In 1913 Ali Jinnah joined the Muslim League, In his political development Ali Jinnah served as president of the Muslim League . The factors that led to the formation of the Pakistani state were religious and cultural factors, economic factors, educational factors and political factors of Ali Jinnah's struggle or efforts in the formation of the Pakistani state. One of his efforts was to carry out negotiations known as the Lucknow pact agreement in 1916.